PENGARUH KUALITAS PRODUK, PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ROYAL GRANDE BATAM - Lase, Juni Kristiani; Syaifullah (SCIENTIA JOURNAL, 2021)
Real estate companies in Indonesia are one of the companies that can respond to these needs, so that it continues to experience very rapid development. To attract consumers, companies must prioritize quality in their production so that consumers can believe in the products made by the company and can enjoy products made with the satisfaction contained in each consumer. Product quality is one of the tools used by retailers to determine their market position. Promotion is an important factor in realizing the goals of a company. Consumer decision making is the process of combining knowledge to select two or more alternatives and to choose one of them. Every company would want consumers' purchasing decisions on the products offered to increase. Due to the increase in number, the company's profits will increase in sales. This study was conducted with the aim of knowing and understanding the effect of product quality, service and promotion on purchasing decisions of Royal Grande Batam. The method used is a data quality test, a classic estimate and a conceptual test. The results of this study are the third variable X has an effect either partially or simultaneously on the Variable Y.